Pengaruh Implementasi Corporate Social Responbility (CSR) terhadap Citra Perusahaan (Studi pada PT PJB UBJ O & M PLTU Rembang) - Imam Dwi Riyanto Dwi Riyanto; Syaiko Rosyidi; Rifqi Suprapto (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2018)
This study aims to prove the influence of CSR program implementation of economic, environmental and social dimension either partially or simultaneously to PT PJB UBJ O & M PLTU Rembang. The sample in this research is ring society 1 PT PJB UBJ O & M PLTU Rembang Leran Village, Trahan, Jurangjero and Pangkalan which amounted to 160 people. Sampling using simple random sampling method and test using multiple linear regression analysis. The results of this study indicate that the economic dimension, environmental dimension and social dimension either partially or simultaneously have a significant positive effect on company image of PT PJB UBJ O & M PLTU Rembang. The result of determination test shows that the economic dimension variable, environmental dimension and social dimension able to explain the dependent variable (corporate image) is 63,9%. While the rest of 37.1% is explained by other causes outside the model not examined in this study. Keywords: CSR, Economics, Environment, Social, Corporate Image